2001
DOI: 10.1093/emboj/20.9.2315
|View full text |Cite
|
Sign up to set email alerts
|

A proline-rich protein binds to the localization element of Xenopus Vg1 mRNA and to ligands involved in actin polymerization

Abstract: A 340 nucleotide element within the 3¢ untranslated region of Vg1 mRNA determines its localization to the vegetal cortex of Xenopus oocytes. To identify protein factors that bind to this region, we screened a cDNA expression library with an RNA probe containing this sequence. Five independent isolates encoded a protein (designated Prrp for proline-rich RNA binding protein) having two RNP domains followed by multiple polyproline segments. Prrp and Vg1 mRNAs are co-localized to the vegetal cortex of stage IV ooc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
106
0
9

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(120 citation statements)
references
References 82 publications
5
106
0
9
Order By: Relevance
“…Human DAZAP-1 is a nucleocytoplasmic shuttling protein (Lin & Yen 2006) and its X. laevis ortholog, PRRP, associates with mRNA localization elements in Vg1 and VegT mRNAs (Zhao et al 2001). However, it is unclear whether DAZAP-1 plays an active role in mRNA localization and its role on these mRNAs appears to be independent of xDAZL.…”
Section: Mechanism Of Dazl-mediated Translational Stimulationmentioning
confidence: 99%
“…Human DAZAP-1 is a nucleocytoplasmic shuttling protein (Lin & Yen 2006) and its X. laevis ortholog, PRRP, associates with mRNA localization elements in Vg1 and VegT mRNAs (Zhao et al 2001). However, it is unclear whether DAZAP-1 plays an active role in mRNA localization and its role on these mRNAs appears to be independent of xDAZL.…”
Section: Mechanism Of Dazl-mediated Translational Stimulationmentioning
confidence: 99%
“…Vg1RBP (also known as Vera) is a protein implicated in localizing Vg1 mRNA to the vegetal cortex during Xenopus oogenesis (Deshler et al+, 1998;Havin et al+, 1998;Zhang et al+, 1999;Kwon et al+, 2002)+ One of the bestcharacterized localized maternal RNAs in Xenopus, Vg1 mRNA encodes a TGF-b-like factor involved in mesoderm induction and left-right axis formation+ Vg1 mRNA translocation to and anchoring at the vegetal cortex involves microtubules and microfilaments, respectively, and is mediated by the 340-nt 39 UTR vegetal localization element (VLE) defined in microinjection assays (Yisraeli et al+, 1990;Mowry & Melton, 1992; reviewed in King et al+, 1999;Palacios & St+ Johnston, 2001;Yaniv & Yisraeli, 2001;Kloc et al+, 2002)+ Vg1 mRNA is not translated until the mRNA is localized, reflecting the tight control of RNA translation and localization shown to be critical for pattern formation in Drosophila (Palacios & St+ Johnston, 2001;Kloc et al+, 2002)+ The 250-nt UA-rich element that represses Vg1 mRNA translation is also located in the 39 UTR, distinct from and downstream of the VLE (Wilhelm et al+, 2000;Otero et al+, 2001)+ Several proteins interact specifically with the VLE (Mowry, 1996), including Vg1RBP/Vera (Deshler et al+, 1998;Havin et al+, 1998;Zhang et al+, 1999), hnRNP I/PTB (Cote et al+, 1999), and PrrP (Zhao et al+, 2001), all of which colocalize with Vg1 mRNA and are thought to play a role in the localization process+ Vg1RBP/Vera and hnRNP I bind the pyrimidine-rich VM1 and E2 motifs which are repeated three to five times throughout the VLE; mutation or deletion of these elements abolishes protein-binding and RNA localization (Deshler et al+, 1998;Havin et al+, 1998;Cote et al+, 1999;Bubunenko et al+, 2002;Kwon et al+, 2002)+ Vg1RBP mediates the association of Vg1 RNA with microtubules in Xenopus oocytes (Elisha et al+, 1995), whereas PrrP has been reported to bind to ligands involved in actin polymerization (Zhao et al+, 2001)+ Although these data strongly implicate these proteins in mediating Vg1 mRNA localization, the actual binding sites of Vg1RBP/ hnRNP I/P...…”
Section: Introductionmentioning
confidence: 99%
“…LEs recruit proteins to form a localization complex. Although proteins that exclusively interact with LEs from early localizing RNAs and that could mediate the entrapment in the MC have not been identified to date, a number of proteins that interact with the localization element of the late localizing Vg1 mRNA have been identified; they include Vg1RBP, hnRNP I, Prrp, VgRBP71/KSRP, XStaufen 1, and 40LoVe (15,(22)(23)(24)(25)(26)(27). Interestingly, mitochondrial cloud localization elements of all early pathway RNAs tested to date can enter the late localization pathway if injected into stage III/IV oocytes, suggesting that they are able to recruit late transport proteins (17, 28 -31).…”
mentioning
confidence: 99%
“…VgRBP71/KSRP and 40LoVe can also be detected in the nucleus, but whether they are indeed part of a nuclear transport RNP remains to be determined (26,27). The reassembly step in the cytoplasm includes the recruitment of additional proteins; whereas hnRNP I, Vg1RBP, Prrp, XStaufen 1, and 40LoVe accompany the localizing RNA in the vegetal cytoplasm and get enriched at the cortex (15,25,27,32,34,35), VgRBP71/KSRP is found throughout the cytoplasm with a slight enrichment at the animal cortex (26). Rather than directly participating in the vegetal transport, VgRBP71/KSRP has been suggested to translationally activate cortical Vg1 mRNA by stimulating a nuclease that cleaves off the Vg1 translational control element (TCE) (36).…”
mentioning
confidence: 99%
See 1 more Smart Citation